The Edge of Awareness : An International Itinerant Exhibition of contemporary Art organized by Art for The World for the 50th Anniversary of the World Health Organization in Geneva, New York, Sao Paulo, New Delhi, 1998-1999. - World Health Organization; Angelidakis, Andreas; Arienti, Stefano; Assaad, Fawzia; Aubral, François; Bester, Willie; Boonma, Montien; Carvalho, Mario César; Chen, Zhen; De Barros, Fabiana; Enwezor, Okwui; Fust, Walter; et al. (Milano : Edizioni Charta, 1998)
Acconci, Vito ; Amer, Ghada ; Arienti, Stefano ; Jr., Joe Ben ; Bester, Willie ; Boonma, Montien ; Collishaw, Mat ; De Barros, Fabiana ; Defraoui, Silvie ; Ennadre, Touhami ; Galdeano, Juan ; Gygi, Fabrice ; Hakansson, Henrik ; Jaar, Alfredo ; Kabakov, Ilya ; Kcho ; Kozaris, Dimitris ; LeWitt, Sol ; Carpinteros, Los ; Manzelli, Margherita ; Mekuria, Salem ; Miyajima, Tatsuo ; Mullican, Matt ; Oguibe, Olu ; Ouattara, Mohamed Sékou ; Perlingeiro, Maria Carmen ; Rauschenberg, Robert ; Reamillo & Juliet ; Ribenboim, Ricardo ; Rimzon, N.N. ; Rios, Miguel Angel ; Ristelhueber, Sophie ; Rodwittiya, Rekha ; Serrano, Teresa ; Steir, Pat ; Suljevic, Alma ; Thiel, Frank ; Varejao, Adriana ; Ward, Nari ; Chen Zhen
biografie
An International Itinerant Exhibition of Contemporary Art organized by ART for the WOrld for the 50th Anniversary of the World Health Organization in Geneva, New York, São Paulo, New Delhi, 1998-1999
Engels
Engels & Frans
Frans
boek